JUAL BELI PADA RESTORAN DENGAN SISTEM ALL YOU CAN EAT (AYCE) MENURUT SYAIKH PROF. DR. SA’AD ASY-SYATSRI - Muthia Nur Aziza; Anwar Hafidzi (LP2M and Shariah Faculty of The Pontianak State Institute of Islamic Studies, 2023)
Buying and selling is something that is never separated from the needs of everyone, especially buying and selling food as a means of human survival. All You Can Eat restaurant is a restaurant or place to eat that offers food to customers/consumers with a pay-as-you-go concept can eat as much as they want within a certain time limit, meaning that each visitor to the restaurant is given the freedom to choose what type of food and how much food they want with nominal payment and time determined by the restaurant. Every food they take will not be the same portion between one another and the money that has been set. This is what causes problems related to the existence of elements of gharar or jahalah (obscurity) in such a system. A qualitative approach was used in this study by reviewing several literature reviews originating from various references as reference material in this study. Shaykh Prof. Dr. Sa'ad As-Syatsri revealed that the act was permissible and there was no problem with it because the harm that was caused was only a little and it was forgiven. It's the same as when someone wants to go to a public toilet, he will pay the fee, even though he may use a lot of water or a little.